ANALISIS KEMAMPUAN HIGNER THINGKING SKILL (HOTS)MATEMATIS SISWA PADA MATERI GEOMETRI - Gracea Roindah Damanik; Friska Ledina Situngkir (Lembaga Sepercenter, 2026)
Higher Order Thinking Skills (HOTS) are essential competencies that students must develop to meet the demands of 21st-century education, as they play a crucial role in fostering critical, creative, logical, and systematic thinking in solving mathematical problems. Geometry is one of the mathematical domains that strongly requires HOTS because it involves spatial reasoning, conceptual understanding, analytical thinking, and problem-solving skills. However, numerous studies have reported that students' mathematical HOTS in geometry remain relatively low. Therefore, this study aimed to analyze students' mathematical Higher Order Thinking Skills (HOTS) in geometry based on three cognitive indicators: analyzing (C4), evaluating (C5), and creating (C6). This study employed a qualitative descriptive research design involving 30 eighth-grade students from a junior high school in Medan, Indonesia, selected through purposive sampling. Data were collected using six HOTS-based essay questions that had been validated by mathematics education experts and classroom teachers, followed by semi-structured interviews and documentation of students' written responses. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data display, and conclusion drawing and verification. Data credibility was ensured through method triangulation. The findings revealed that students' mathematical HOTS were generally very low, with an overall achievement rate of 18.34%. The achievement level for the analyzing (C4) indicator reached 28.34% (low category), while the evaluating (C5) and creating (C6) indicators achieved only 18.34% and 8.34%, respectively, both classified as very low. The analysis of students' responses indicated that most students experienced difficulties in understanding geometric concepts conceptually, evaluating solution strategies using logical reasoning, and generating alternative or creative problem-solving approaches. The results also demonstrate that students' performance declined as the cognitive demand of the tasks increased. The novelty of this study lies in its comprehensive analysis of students' errors across each HOTS indicator, providing detailed diagnostic information regarding conceptual misunderstandings, reasoning deficiencies, and problem-solving limitations. These findings are expected to serve as empirical evidence for mathematics teachers in designing more effective instructional strategies and assessment practices aimed at enhancing students' Higher Order Thinking Skills in geometry learning.